Barrier protective effects of rosmarinic acid on HMGB1‐induced inflammatory responses in vitro and in vivo12. Issue 5 (28th January 2013) - Yang, Eun‐Ju; Ku, Sae‐Kwang; Lee, Wonhwa; Lee, Sangkyu; Lee, Taeho; Song, Kyung‐Sik; Bae, Jong‐Sup
Abstract High mobility group box 1 (HMGB1) protein is a crucial cytokine that mediates response to infection, injury, and inflammation. Rosmarinic acid (RA) is an important component of the leaves of Perilla frutescens and has neuroprotective, anti‐microbial, anti‐oxidant, and anti‐cancer effects but little is known of its effects on HMGB1‐mediated inflammatory response. Here, we investigated this issue by monitoring the effects of RA on the lipopolysaccharide (LPS) or cecal ligation and puncture (CLP)‐mediated release of HMGB1 and HMGB1‐mediated modulation of inflammatory responses. RA potently inhibited the release of HMGB1 and down‐regulated HMGB1‐dependent inflammatory responses in human endothelial cells. RA also inhibited HMGB1‐mediated hyperpermeability and leukocyte migration in mice. Furthermore, RA reduced CLP‐induced HMGB1 release and sepsis‐related mortality. Given these results, RA should be viewed as a candidate therapeutic agent for the treatment of various inflammatory diseases via inhibition of the HMGB1 signaling pathway. J. Cell. Physiol. © 2012 Wiley Periodicals, Inc.